PROPOSAL FOR READJUSTMENT OF PHYSICAL ARRANGEMENT IN THE TEXTILE INDUSTRY: a case study in the clothing production line - Santos, Breno Augusto Pereira dos; Volante, Carlos Rodrigo (Revista Interface Tecnológica, 2020)
Historically, the textile market has become increasingly competitive. With the recent changes and fashion trends, the focus becomes the speed which organizations are flexible and meet demand changes. For that, it is necessary that the organizations have an adequate physical arrangement, capable to make it possible to place orders efficiently, allowing their permanence in the market, growth and profitability. This article discusses the importance of a good physical arrangement and its operating system to determine a company’s productive capacity and aims to propose a readjustment in the physical arrangement of the company under study. A case study was carried out on a production line in the textile industry and an improvement proposal was presented. At the end of the study, a new physical arrangement for organization was presented, accompanied by the analysis of results, allowing a well-defined and planned physical arrangement to reduce waste and increase the organization’s profitability.